Analisis Kandungan Calsium (Ca) Kalium (K) Pada Sedimen Danau Limboto Menggunakan Metode AAS - Annisa Untuba; Ishak Isa; Wiwin Rewini Kunusa; Jafar La Kilo (Jambura Journal of Chemistry, 2022)
ABSTRACT Lake Limboto is a natural resource currently owned by Gorontalo Province. Lake Limboto has played a role as a source of income for fishermen, flood prevention, irrigation water sources and tourism objects. Sediment is sediment that comes from the breakdown of rocks, or biological materials that are transported through a liquid, and solid materials (sediments) that float in, or are deposited in water. This study aims to determine the content of calcium and potassium in the sediment of Limboto lake, straw, and analysis of Ca and K in liquid organic fertilizer from straw and sediment using the AAS method. The results showed that the levels of calcium (Ca) from the three points in the sediments of the Limboto lake met the SNI standards, namely 0.20, 0.37, 0.59%. Meanwhile, the potassium (K) levels from the three points did not meet the SNI standards, namely 0.15, 0.10, 0.13%, different from those obtained from the analysis of the calcium and potassium content of the straw that met the SNI standards of 0.35% and 1.52. %. In liquid organic fertilizer the content of Ca and K from three points yields little, while the results of Ca content meet the SNI standards of 0.04, 0.05, 0.06%, the results of K levels do not meet the SNI standards, namely 0.09, 0.07, 0.08%. Keywords: Limboto Lake; Straw Sediment; Calcium; Potassium